Warehouse Market in Poland and in Lublin: Conditions, Tendencies and Development Prospects - Piotr Maleszyk; Joanna Szafran (Barometr Regionalny, 2017)
The aim of the analysis was to identify the features and development trends of the warehouse market in Lublin against the background of regional and domestic markets in Poland, and, subsequently, to assess the market’s development prospects and its role in strengthening the economic development of the City of Lublin. Valuable data on the supply and demand side of the warehouse market in Lublin has been collected for the purpose of the article. The analysis of the data on warehouse market development, in Lublin as well as and in regional and domestic markets in Poland in 2015 and 2016, confirmed the market’s solid growth. The prospects of the warehouse market in Lublin are very promising, owing to such factors as: supply of a highly qualified labor force, relatively low labor costs, the improvement of transport infrastructure, the development of the Special Economic Zone Euro-Park Mielec Lublin Subzone, and, last but not least, the effective strategy of attracting investors pursued by the Department of Strategy and Investor Relations of the City Office in Lublin.